Synthesis and Pharmacological Profiles of 6,7-Dihydroxycoumarin and Its Derivatives: A Concise Review - Nameer Zeki; Yasser Fakri Mustafa (University of Mosul, 2023)
Background: Esculetin, scientifically referred to as 6,7-dihydroxycoumarin, functions as the primary bioactive constituent found in Cortex Fraxini (commonly known as ash bark), an ancient Asian medicinal substance. Herbal practitioners utilize the outer layer of the branch or stem bark of Cortex Fraxini for its gentle and safe medicinal properties and its potential as a nutritional component. In contemporary times, the landscape has undergone a notable transformation due to the emergence of a wide range of innovative 6,7-dihydroxycoumarin derivatives. The recent surge of innovation has sparked a heightened interest in understanding the molecular mechanisms that underlie the effects of Cortex Fraxini and 6,7-dihydroxycoumarin in clinical applications. Aim: This succinct review seeks to build up the extensive knowledge accumulated in the past decade concerning the synthesis, pharmacological profiles and principles linked to 6,7-dihydroxycoumarin and its chemical analogues. Furthermore, we aim to provide a concise yet inclusive overview of the unique characteristics of 6,7-dihydroxycoumarin. Conclusion: Satisfying these aims can enhance the comprehension of the diverse possibilities presented by this chemical and its related compounds across different research and application domains.